2020
DOI: 10.21203/rs.3.rs-35962/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lameness in fattening pigs – Mycoplasma hyosynoviae, osteochondropathy and reduced dietary phosphorus level as three influencing factors: A case report

Abstract: BackgroundMultiple diagnostic procedures, their results and interpretation in a case with severe lameness in fattening pigs are described. It is shown that selected diagnostic steps lead to identification of various risk factors for disease development in the affected herd. One focus of this case report is the prioritization of diagnostic steps to verify the impact of the different conditions, which finally led to the clinical disorder. Assessing a sufficient dietary phosphorus (P) supply and its impact on dis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Clinical metabolic bone disease, which can develop due to compromised bone mineralisation caused by dietary imbalances or dysregulations of mineral homeostasis, is a possible cause of lameness and fractures (Madson et al, 2012; Wegner et al, 2020). Due to their rapid growth rate, especially in the late rearing to early finishing phase, and limited sunlight in conventional housing systems, pigs are particularly susceptible to developing rickets (Dittmer & Thompson, 2011; Madson et al, 2012).…”
Section: Dietary Supplementation With 25‐ohd3 Versus Vitamin D3mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical metabolic bone disease, which can develop due to compromised bone mineralisation caused by dietary imbalances or dysregulations of mineral homeostasis, is a possible cause of lameness and fractures (Madson et al, 2012; Wegner et al, 2020). Due to their rapid growth rate, especially in the late rearing to early finishing phase, and limited sunlight in conventional housing systems, pigs are particularly susceptible to developing rickets (Dittmer & Thompson, 2011; Madson et al, 2012).…”
Section: Dietary Supplementation With 25‐ohd3 Versus Vitamin D3mentioning
confidence: 99%
“…Osteochondrosis is a degenerative, multifactorial disorder of the immature skeleton that results in lesions of the growth plate cartilage (Olstad et al, 2015, 2018, 2019) and lameness (Wegner et al, 2020). Sugiyama et al (2013) found in growing pigs (6−10 kg) that dietary supplementation of 50 µg/kg 25‐OHD 3 was able to reduce the incidence of osteochondrotic lesions analysed by macroscopic examination of articular cartilage of the distal humerus (32.4% vs. 59.3%) and distal femur (47.1% vs. 87.5%).…”
Section: Dietary Supplementation With 25‐ohd3 Versus Vitamin D3mentioning
confidence: 99%